Taurine trial in succinic semialdehyde dehydrogenase deficiency and elevated CNS GABA - Pearl, Phillip L. (Lippincott Williams & Wilkins, 2014)
OBJECTIVES: The objective of this open-label study was primarily to assess the effect of taurine on adaptive behavior and secondarily to collect safety and tolerability data in patients with succinic semialdehyde dehydrogenase deficiency. METHODS: In the current study, subjects were titrated weekly from a starting dose of 50 mg/kg/d to a target 200 mg/kg/d, and assessed for safety, tolerability, and adaptive functioning using age-normalized Adaptive Behavior Assessment Scales. RESULTS: Eighteen patients (8 males/10 females, aged 0.5–28 years, mean 12 years) were recruited. Three subjects withdrew because of perceived lack of efficacy. One serious adverse event occurred (hospitalization for hypersomnia) on 16 g/d (200 mg/kg/d), leading to a dose-lowering paradigm with a maximum dose of 10 g/d. Results did not show clinically meaningful improvement in the adaptive domains after taurine therapy. Pre- and posttherapy adaptive scores also demonstrated no statistically significant difference (p > 0.18). CONCLUSIONS: Adaptive behavior did not improve significantly with taurine intervention. Further therapeutic clinical trials including an on-off paradigm using biomarkers are planned. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with succinic semialdehyde dehydrogenase deficiency, taurine does not significantly improve adaptive behavior. The study is rated Class IV because of the absence of a control group.